Peningkatan Keterwakilan Perempuan di Lembaga Legislatif Kota Padang oleh Kesatuan Perempuan Partai Golkar - Maharani, Vina Kurnia; Rafni, Al; Suryanef, Suryanef; Fatmariza, Fatmariza (Journal of Civic Education, 2024)
This article aims to examine the efforts of the Women’s Unity of the Golkar Party (KPPG) in enhancing women's representation in the legislative body through the recruitment process of prospective legislative candidates in the 2019 elections in Padang City. Employing a qualitative descriptive method, data collection was carried out through interviews and document analysis, while the validity of the data was tested using source triangulation by comparing interview results with documentary evidence from various relevant sources. The data analysis followed three key steps: data reduction, data presentation, and conclusion drawing. The findings indicate that KPPG’s efforts include: a) engaging in social services and community activities, b) providing political education through seminars, c) conducting orientation training for cadre members, d) organizing training of trainers, and e) offering campaigner training. However, KPPG faces several obstacles in increasing women's representation, including: a) the entrenched patriarchal culture in the Minangkabau community, b) lack of support or permission from husbands within the family environment, c) low interest among women in participating in politics, and d) financial limitations, where some potential candidates are unwilling to bear the costs required for candidacy.